The effect of financial literacy financial inclusion and financial management on financial perfomance in MSMEs in the city of Semarang - Rokhmad Budiyono; Arini Novandalina; Ukie Tukinah (Enrichment : Journal of Management, 2023)
Indonesia is a member United States of america of the ASEAN enterprise (Association of South East Asia Nations). The implementation of the MEA (ASEAN Economic Community) on the end of 2015 is a mission for Indonesia. The purpose of this take a look at was to decide the effect of economic literacy, financial inclusion and financial control on the economic performance of MSMEs in Semarang City.The population on this examine is 11,910 MSME gadgets in the metropolis of Semarang. The sampling method uses non-probability sampling inside the shape of accidental sampling so that the entire pattern is 388 gadgets. Financial literacy, monetary inclusion and financial control are impartial variables even as monetary performance is the dependent variable. The analytical technique used is the classical assumption test, more than one linear regression check and hypothesis checking out.The outcomes confirmed that the financial literacy t-check consequences had been 1.733 <t table 1.966 and the sig. Of 0.084 > zero.05 so that H1 which states monetary literacy on economic overall performance is rejected. Financial inclusion t-check outcomes of 0.082 <t table 1.966 and sig. Of 0.935 > 0.05 so that H2 which states financial inclusion on economic performance is rejected. The outcomes of the t-take a look at for economic management are 5.940 > t table 1.966 and the sig. Of zero.000 <0.05 so that H3 which states financial inclusion on financial overall performance is prevalent.